To the definition of «administrative responsibility» - Бородін, Іван Лук'янович; Круглов, Валерій Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article examined the concepts of the administrative responsibility that connected with definition. After the analysis of the different points of view authors have come to conclusion that the administrative responsibility is one of types of the legal responsibility. There is legal relations between the person thatmade act breaking established by the Code about administrative offences an interdiction and the state connected with application or refusal of application to the specified person of sanctions expressing an assessmentof its behavior and with execution of the made decision.